Determinants of stunting and severe stunting among Burundian children aged 6-23 months: evidence from a national cross-sectional household survey, 2014 - Sandra Nkurunziza; Bruno Meessen; Jean-Pierre Van geertruyden; Catherine Korachais (BMC, 2017)
Abstract Background Burundi is one of the poorest countries and is among the four countries with the highest prevalence of stunting (58%) among children aged less than 5 years. This situation undermines the economic growth of the country as undernutrition is strongly associated with less schooling and reduced economic productivity. Identifying the determinants of stunting and severe stunting may help policy-makers to direct the limited Burundian resources to the most vulnerable segments of the population, and thus make it more cost effective. This study aimed to identify predictors of stunting and severe stunting among children aged less than two years in Burundi. Methods The sample is made up of 6199 children aged 6 to 23 months with complete anthropometric measurements from the baseline survey of an impact evaluation study of the Performance-Based financing (PBF) scheme applied to nutrition services in Burundi from 2015 to 2017. Binary and multivariable logistic regression analyses were used to examine stunting and severe stunting against a set of child, parental and household variables such as child's age or breastfeeding pattern, mother's age or knowledge of malnutrition, household size or socio-economic status. Results The prevalence of stunting and severe stunting were 53% [95%CI: 51.8-54.3] and 20.9% [95%CI: 19.9-22.0] respectively. Compared to children from 6-11 months, children of 12-17 months and 18-23 months had a higher risk of stunting (AdjOR:2.1; 95% CI: 1.8-2.4 and 3.2; 95% CI: 2.8-3.7). Other predictors for stunting were small babies (AdjOR=1.5; 95% CI: 1.3-1.7 for medium-size babies at birth and AdjOR=2.9; 95% CI: 2.4-3.6 for small-size babies at birth) and male children (AdjOR=1.5, 95% CI: 1.4-1.8). In addition, having no education for mothers (AdjOR=1.6; 95% CI: 1.2-2.1), incorrect mothers' child nutrition status assessment (AdjOR=3.3; 95% CI: 2.8-4), delivering at home (AdjOR=1.4; 95% CI: 1.2-1.6) were found to be predictors for stunting. More than to 2 under five children in the household (AdjOR=1.45; 95% CI: 1.1-1.9 for stunting and AdjOR= 1.5; 95% CI: 1.2-1.9 for severe stunting) and wealth were found to be predictors for both stunting and severe stunting. The factors associated with stunting were found to be applicable for severe stunting as well. Conclusion Mother's education level, mother's knowledge about child nutrition status assessment and health facility delivery were predictors of child stunting. Our study confirms that stunting and severe stunting is in Burundi, as elsewhere, a multi-sectorial problem. Some determinants relate to the general development of Burundi: education of girls, poverty, and food security; will be addressed by a large array of actions. Some others relate to the health sector and its performance - we think in particular of the number of children under five in the household (birth spacing), the relationship with the health center and the knowledge of the mother on malnutrition. Our findings confirm that the Ministry of Health and its partners should strive for better performing and holistic nutrition services: they can contribute to better nutrition outcomes.